Secure and resource-efficient communications for telemedicine systems. (March 2022) - Chen, Hanlin; Ding, Ding; Zhang, Lei; Zhao, Cheng; Jin, Xin
Highlights: A novel reusable improved Juels-Sudan (RIJS) fuzzy extractor using the shared random Bio-pool (SRB) technique is proposed. Based on the RIJS and dynamical biometric model (DBM), a secure and efficient bio-cryptography mode for remote communications is realized. The task migration deployment strategy (TMDS) is proposed to solve the problem of huge biometric signals and limited resources. A secure and resource-efficient communication scheme is designed and implemented, and excellent experimental results are obtained. Abstract: This paper designs and implements a secure and resource-efficient communication scheme for electrocardiogram (ECG) telemedicine systems. In the authentication and key agreement phase, a novel reusable Improved Juels-Sudan (IJS) fuzzy extractor with the Shared Random Bio-pool (SRB) technique is proposed to prevent the information leakage of personal biometrics. By exploiting the dynamical biometric model (DBM) for generating synthetic ECG signals, the reusable IJS fuzzy extractor could accomplish identity authentication, generation and distribution of keys, and periodic rekeying in a zero-leakage, user no-involvement and efficient way. In data encryption and transmission phase, a Task Migration Deployment Strategy (TMDS) is adopted to improve the efficiency of various resources. Experiments show that the scheme has high security, including information zero-leakage, low false acceptance rate (FAR) and false rejection rate (FRR), as well as saves various resources with a ratio of 385.8:1, which improves by at least 294.8% compared to the existing schemes. Graphical abastract: Image, graphical abstract